The Profile Of Self-Acceptance Of Parents Of Children With Special Needs And Developmental Disabilities - Mukhlis, Akhmad; Aniswari, Pria Dita; Fitriah, Nurlaeli; Erfantinni, Imroatul Hayyu; Susanti, Rikza Azharona (Universitas Ahmad Dahlan, 2023)
The ability of parents to accept the condition of their children with special needs has a positive impact on the process of handling children. This study aims to explore the experiences of parents who have children with special needs and developmental disorders using Elisabeth Kübler-Ross' theoretical perspective regarding the stages of grief and forms of acceptance. This qualitative phenomenological research focuses on parents' self-acceptance as a phenomenon. The research subjects were selected using a purposive sampling technique, and three parents of children with special needs and developmental disorders aged 5-7 years were identified. Research data was collected using direct interviews, in-depth observations, and online communication media. The data were processed and reduced manually by the researchers before being presented. The results showed that all subjects went through the stages of acceptance according to the stages of grief theory, but the stages experienced by the subjects varied slightly. The rejection stage was experienced only by Subject 1 and Subject 2; the anger stage by Subject 2 and Subject 3; the bargaining stage by Subject 1, Subject 2, and Subject 3; the depression stage by Subject 1 and Subject 3; and the acceptance stage by all three subjects. The process of parental acceptance of children with special needs has a direct impact on the parenting model and the fulfillment of children's rights in everyday life. Therefore, good acceptance skills are crucial for parents of children with special needs, enabling them to feel comfortable and guide their children towards achieving self-actualization.